Multiplex, Rapid, and Sensitive Isothermal Detection of Nucleic-Acid Sequence by Endonuclease Restriction-Mediated Real-Time Multiple Cross Displacement Amplification - Wang, Yi; Wang, Yan; Zhang, Lu; Liu, Dongxin; Luo, Lijuan; Li, Hua; Cao, Xiaolong; Liu, Kai; Xu, Jianguo; Ye, Changyun (Frontiers in Microbiology, 2016)
We have devised a novel isothermal amplification technology, termed endonuclease restriction-mediated real-time multiple cross displacement amplification (ET-MCDA), which facilitated multiplex, rapid, specific and sensitive detection of nucleic-acid sequences at a constant temperature. The ET-MCDA integrated multiple cross displacement amplification strategy, restriction endonuclease cleavage and real-time fluorescence detection technique. In the ET-MCDA system, the functional cross primer E-CP1 or E-CP2 was constructed by adding a short sequence at the 5’ end of CP1 or CP2, respectively, and the new E-CP1 or E-CP2 primer was labelled at the 5’ end with a fluorophore and in the middle with a dark quencher. The restriction endonuclease Nb.BsrDI specifically recognized the short sequence and digested the newly synthesized double-stranded terminal sequences (5’ end short sequences and their complementary sequences), which released the quenching, resulting on a gain of fluorescence signal. Thus, the ET-MCDA allowed real-time detection of single or multiple targets in only a single reaction, and the positive results were observed in as short as 12 minutes, detecting down to 3.125 fg of genomic DNA per tube. Moreover, the analytical specificity and the practical application of the ET-MCDA were also successfully evaluated in this study. Here we provided the details on the novel ET-MCDA technique and expounded the basic ET-MCDA amplification mechanism.